Revisiting the Asymptotic Dynamics of General Relativity on ads3 - Pino-Rozas, M (Springer Verlag, 2018)
The dual dynamics of Einstein gravity on AdS3 supplemented with boundary conditions of KdV-type is identified. It corresponds to a two-dimensional field theory at the boundary, described by a novel action principle whose field equations are given by two copies of the “potential modified KdV” equation. The asymptotic symmetries then transmute into the global Noether symmetries of the dual action, giving rise to an infinite set of commuting conserved charges, implying the integrability of the system. Noteworthy, the theory at the boundary is non-relativistic and possesses anisotropic scaling of Lifshitz type. © 2018, The Author(s).